Inside Back Cover: Zinc Porphyrin Metal‐Center Exchange at the Solid–Liquid Interface (Chem. Eur. J. 25/2016). Issue 25 (25th May 2016) - Franke, Matthias; Marchini, Florencia; Jux, Norbert; Steinrück, Hans‐Peter; Lytken, Ole; Williams, Federico J.
Abstract : Porphyrin demetalation and metal‐center exchange were investigated at the solid–liquid interface by exposing adsorbed zinc tetraphenylporphyrin on Au(111) to aqueous solutions. Metal‐center exchange with copper ions at neutral pH took place rapidly, but demetalation under acidic conditions was not observed. This difference to liquid‐phase chemistry is explained by the surface acting as a ligand for the zinc ion. More information can be found in the Full Paper by O. Lytken, F. J. Williams et al. onpage 8520 ff.